Exploration Of The Use Of Early Childhood Student Worksheets (LKS) Media Based On Multiple Intelligence - Hasanah BZ, Siti Novita Widayatul; Wahidah, Finadatul (Cakrawala Journal is a scientific journal published by Nahdlatul Ulama Islamic Institute (IAINU) Kebumen. This journal focuses on the Islamic Education Management Study and Social Studies which is published twice a year.IAINU Kebumen, 2024)
Learning media is a forum for educators in an educational institution to convey material that will be delivered to students. There are many learning media used by educators, one of which is the LKS used by teachers at RA Ulul Albab, but the LKS used by teachers -Teachers at RA Ulul Albab is the work of teachers at that institution. This research describes the process of preparing Multipe Intelligence-based worksheets with an independent curriculum at RA Ulul Albab, Kaliwates District, Jember Regency. This research uses a qualitative approach. This determination technique uses a purposive sampling technique. The data collection techniques are interviews, observation, and documentation. The data analysis technique uses Miles and Huberman. Based on the research results, it can be concluded that the preparation of Multiple Intelligence-based LKS can meet the achievement standards for children at RA Ulul Albab, and this is proven by the many institutions both in East Java Province and outside Java that use LKS that have been prepared by RA Ulul Albab teachers and the team. Another. The preparation of multiple intelligence-based LKS also combines the latest curriculum so that every year, there are updates to the LKS that have been prepared. The existence of LKS that have been prepared by RA Ulul Albab teachers is very helpful for teachers in the teaching and learning process; apart from the attractive appearance, the LKS contains more pictures than writing, so that students are interested in the LKS. Evaluation activities are always carried out by the LKS preparation team once a year so that the LKS prepared always follows the latest curriculum and is based on Multiple Intelligence in accordance with the vision and mission of RA Ulul Albab Jember.